Analisis Tentang Praktik Ba’i Al Wafa’ Sawah di Desa Parannapa Jae Menurut Perspektif Ekonomi Islam - Siti Armia Daulay; Junda Harahap; Aminah Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The practice of Ba'i Al Wafa' in an Islamic Economic Perspective is an agreement that occurs between two parties, namely the seller (the owner of the rice field) and the buyer, whereby the rice field can return to the seller (the owner of the rice field) if the rice field can be redeemed by the seller (the owner of the rice field). If the field has not been redeemed, the field will remain in the possession of the buyer. (2) Analysis of the Practice of Ba'i Al Wafa' Sawah in Parannapa Jae Village, Barumun Barat District, Padang Lawas Regency according to an Islamic economic perspective, namely buying and selling that takes place on condition that the goods being sold can be repurchased by the seller when the agreed grace period has arrived. Based on an explanation of the practice and theory of bai' al wafa', it can be said that the practice of buying and selling that took place in the village of Parannapa Jae, Barumun Barat District, Padang Lawas Regency, in practice was in accordance with an Islamic economic perspective.